2016
DOI: 10.1007/s00267-016-0712-4
|View full text |Cite
|
Sign up to set email alerts
|

Management Options During the 2011–2012 Drought on the Apalachicola River: A Systems Dynamic Model Evaluation

Abstract: The Apalachicola-Chattahoochee-Flint River basin (ACF) is a large watershed in the southeastern United States. In 2012, the basin experienced the second year of a severe drought and the third multi-year drought in the last 15 years. During severe droughts, low reservoir and river levels can cause economic and ecological impacts to the reservoir, river, and estuarine ecosystems. During drought, augmenting Apalachicola River discharge through upstream reservoir releases and demand management are intuitive and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Remote Sens. 2018, 10, 1390 6 of 23intermittently observed from 2011-2013[36]. Note that Tahsin et al[20] reported similar findings regarding NDVI dynamics showing drops at 2005, 2009 and 2011-2012.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Remote Sens. 2018, 10, 1390 6 of 23intermittently observed from 2011-2013[36]. Note that Tahsin et al[20] reported similar findings regarding NDVI dynamics showing drops at 2005, 2009 and 2011-2012.…”
mentioning
confidence: 58%
“…Apalachicola Bay was impacted by Hurricane Elena, Hurricane Dennis, Hurricane Claudette in 1985, 2005 and 2013, respectively. Tropical storms followed by flood impacted Apalachicola Bay during 1994-1996 and droughts were intermittently observed from 2011-2013 [36]. Note that Tahsin et al [20] Horizontal line (red line) in (a,b), in each box indicates median demarcating 50% data either above or below the median whereas the dashed (brown) horizontal lines represent the average 25th and 75th percentiles for the two types of the wetlands studied here (corresponding percentile values are written inside parenthesis adjacent to the dashed brown lines).…”
Section: Normalized Difference Vegetation Index Derived Studiesmentioning
confidence: 99%
“…The remaining reservoirs, including those on the Flint River, are run-of-the-river-type facilities with little or no storage capacity. The ratio of reservoir storage capacity to annual flow in the lower ACF basin is small relative to other river basins in the USA; management options in this basin consequently are more limited than in other basins (Leitman et al 2015b). The ACF basin has the storage capacity to hold less than 3 months of average flow, whereas the Colorado basin has over 3 years of average flow in storage (Vano and Lettenmaier 2014).…”
Section: Basin Description and Water Managementmentioning
confidence: 98%
“…The Apalachicola-Chattahoochee-Flint watershed is unique among the systems that are known to support Gulf Sturgeon because the Jim Woodruff Lock and Dam (JWLD), which was completed in 1957, blocks upstream passage to approximately 78% of the historic riverine habitat (Wooley and Crateau 1985) and is a possible discrete management unit for Gulf Sturgeon as described by the USFWS and Gulf States Marine Fisheries Commission (1995). The Apalachicola River is also part of ongoing legal action between the basin states of Florida and Georgia that is related to water use within the basin and its potential effects on riverine and estuarine ecosystems (Ruhl 2005;Pine et al 2015;Leitman et al 2016).…”
Section: Study Sitementioning
confidence: 99%